Memory and Anticipation of Income: New Empirical Support for an Old Theory of the Utility Function. (30th October 2018) - Knight, John; Gunatilaka, Ramani
Abstract : The paper contrasts early theories of the utility function (starting with Bentham and elaborated by Jevons) with the modern theory (laid down by Fisher and Samuelson). The former include in the utility function not only the sensation of current events but also the memory of past events and the anticipation of future events, whereas the latter treat current utility as a function only of current consumption and not of consumption at other times. The alternative hypotheses are tested by introducing both past and expected future income into the estimated subjective well‐being function, using an appropriate data set for China. The conditions under which the happiness score is a proxy for utility are analysed. Efforts are made to examine whether the associations between the introduced variables and the happiness score are causal effects. The tests, involving detailed analysis of reference points, both reference times and reference groups, favour the early theories. Implications for the analysis of some aspects of economic behaviour are drawn.